Quercetin and polycystic ovary syndrome - Ma, Congshun; Xiang, Qianru; Song, Ge; Wang, Xuefei (Frontiers in Pharmacology, 2022)
Polycystic ovary syndrome (PCOS) is a reproductive endocrine disease, and results to opsomenorrhea or amenorrhea, hairy, acne, acanthosis, infertility, abortion. In the long term, PCOS may also increase the risk of endometrial cancer, diabetes, hypertension, dyslipidemia and other diseases. There is no specific drug for PCOS due to the unclearness of the cause and pathogenesis, and current treatments for PCOS only target certain symptoms. Quercetin is a flavonoid drug from nature, widely found in Chinese herbal medicines, fruits, leaves, vegetables, seeds and plants roots. Studies on other diseases have found that quercetin has anti-oxidant, anti-inflammatory, anti-insulin resistance, anti-cancer and other effects. Some studies have shown that serum testosterone (T), luteinizing hormone (LH), the LH/follicule-stimulating hormone (FSH) ratio, fasting glucose, fasting insulin, HOMA-IR and lipid levels are reduced in PCOS patients with quercetin treatment. However, the mechanisms of quercetin in PCOS patients have not been completely elucidated. In this review, we retrospect the current risk factors for the occurrence of PCOS, the origin and related basic studies of quercetin, the effects and mechanism of quercetin in PCOS model rats, the changes in relevant parameters after quercetin administration in PCOS patients, and the potential quercetin therapeutic applications.